The electronic encyclopedia (Danbury, Conn., 1990)
Searchable database containing all twenty-one volumes of the Academic American encyclopedia, drawings, photographs, and pictures. Includes electronic bookmark, split screen, and picture index features.
Keywords: Bách khoa toàn thư điện tử,Electronic encyclopedias